Employment in South Asia A New Dataset - Beyer, Robert Carl Michael (The World Bank, 2019)
This paper presents a new dataset of comparable employment indicators for South Asian countries, constructed from more than 60 primary data sources from 2001 to 2017. The main contribution of the paper is to curate the information provided by individual respondents to censuses and surveys, in a way that is consistent across countries and over time. The usefulness of the dataset is illustrated by conducting a rigorous assessment of employment characteristics, of changes in employment over time, and of the short- and long-run relationship between economic growth and employment growth in South Asia. The exercise shows that agriculture still employs the majority of the working-age population across the region and, except in Sri Lanka, more than half of the employment is self-employment or unpaid family work. The paper also shows that employment rates are generally decreasing in South Asia, and that in some countries female employment rates are falling rapidly. Seasonal growth patterns are shown to affect the composition of employment, while non-seasonal changes in short-run growth affect the overall level of employment. The paper estimates that, in the long run, one percentage point growth of gross domestic product has led on average to a 0.34 percent increase in employment